2014
DOI: 10.1063/1.4892094
|View full text |Cite
|
Sign up to set email alerts
|

Local stress-induced effects on AlGaAs/AlOx oxidation front shape

Abstract: The lateral oxidation of thick AlGaAs layers (>500 nm) is studied. An uncommon shape of the oxide tip is evidenced and attributed to the embedded stress distribution, inherent to the oxidation reaction. Experimental and numerical studies of the internal strain in oxidized AlxGa1−xAs/GaAs structures were carried out by dark-field electron holography and finite element methods. A mapping of the strain distribution around the AlGaAs/oxide interface demonstrates the main role of internal stress on the shapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 21 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…As AlOx is amorphous and not stoichiometric, its exact mechanical properties are unknown. As an approximation, we used γ-Al 2 O 3 parameters (Young modulus: E = 400 GPa, υ = 0.21) [20]. We have considered an elastic strain of 13% in the oxide layer along the direction perpendicular to the substrate plane.…”
Section: Modeling and Discussionmentioning
confidence: 99%
“…As AlOx is amorphous and not stoichiometric, its exact mechanical properties are unknown. As an approximation, we used γ-Al 2 O 3 parameters (Young modulus: E = 400 GPa, υ = 0.21) [20]. We have considered an elastic strain of 13% in the oxide layer along the direction perpendicular to the substrate plane.…”
Section: Modeling and Discussionmentioning
confidence: 99%
“…2 shows a top-view near-infrared optical microscope image of one of the fabricated micro-disks. We observed that the oxidation depths of the two AlGaAs layers are actually not strictly identical, a phenomenon we believe to be the result of oxide-induced strain distribution in the asymmetric vertical structure [14]. The bottom waveguide aperture width was measured to be ∼3.7 μm by using a focused ion beam (FIB) and scanning electron microcopy (SEM) characterizations, while the upper confining layer aperture width was found to be ∼1.2 μm larger.…”
Section: Device Fabricationmentioning
confidence: 97%
“…where C( ⃗, ) is the considered species concentration at position ⃗ and at the oxidation time, t, and � �⃗ stands for the diffusion tensor. The v( ⃗, ) coefficient represents the convection term (including bulk convection and other diffusing-limiting phenomena such as strain-induced effects [20] or/and pore blocking [30]). The associated boundary conditions are set by the gas transfer at the edge of the mesa (external periphery, ⃗ , with gas transport coefficient, h) and by the consumption/production of the element at the oxide/semiconductor interface ( ⃗ ) with an orientation-dependent distribution of reaction rates, { �⃗ }:…”
Section: General Presentationmentioning
confidence: 99%
“…depend on the geometrical characteristics of the interface between the (unoxidized) semiconductor and the oxidized areas resulting from the partial lateral oxidation of mesas whose etched sidewalls have been exposed to water. To address the above-mentioned requirement and potentially enhance the device manufacturability, several models have been developed to reproduce the process kinetics [12] [13] [14] [15] [16] [17] [18] [15] [19] [20] [21] [22]. These models are, in essence, all based on the empirical model established by Deal and Grove which describes and quantifies the temporal evolution of the oxidation depth of surface oxidized silicon wafers in terms of the interplay between the diffusive and reactive nature of the process [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation